An Assessment of Bulk Metallic Glasses for Microelectromechanical System Devices. (21st August 2013) - Chauhan, Aditya; Vaish, Rahul
Abstract : Metallic glasses were born purely of academic interest and earlier commercial attempts were limited due to the low thickness of the samples. However, with the successful fabrication of bigger samples using multicomponent system, there has been renewed interest in the commercial applicability of bulk metallic glasses (BMGs) as they offer promising mechanical, tribological and other properties which make the commercialization aspect lucrative. Through this study, an attempt has been made to assess the applicability of bulk metallic glasses as a material for Microelectromechanical System (MEMS) applications. Ranking and comparison, with the current MEMS material set, has been made using multiple criteria decision making (MCDM) approach. Performance index (PIs) was calculated using Ashby approach and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) was used to rank the materials on a collective basis. Additional features have been investigated to assess their suitability as a MEMS material. It was observed that BMGs offer promising prospects as a suitable MEMS material based on their overall performance when compared to the current material set being used for MEMS applications.